A new Stomatorhinus (Osteoglossomorpha: Mormyridae) from the Ivindo River, Gabon, West Central Africa - Sullivan, John P.; Hopkins, Carl D. (Zootaxa, 2005)
Stomatorhinus ivindoensis n. sp. is described from the basin of the Ivindo River, a tributary of the Ogooué River, in Gabon, West Central Africa. This species is characterized by its very small size which is not known to exceed 56 mm standard length. It is distinguished from S. fuliginosus from the Congo basin, the only described Stomatorhinus for which all members of the type series are within the size range of S. ivindoensis, by a smaller caudal peduncle depth to length ratio, a narrower head, a greater number of lateral line scales with visible tubes and pores and by rounded caudal fin lobes. It is distinguished from the similar S. polli, also from the Congo basin, by a longer snout, a smaller eye and a greater interorbital width relative to head length. It is distinguished from S. walkeri, the only other species described from the Ogooué River basin, by its smaller size, smaller snout to pectoral fin distance (relative to standard length) and by its reduced numbers of pectoral rays, vertebrae, and lateral line scales with visible tubes and pores. Stomatorhinus ivindoensis is endemic to the Ivindo River basin of Gabon and is allopatrically distributed with respect to S. walkeri which, although found elsewhere in the Ogooué River basin, has never been recorded from the Ivindo River. Stomatorhinus ivindoensis may be the smallest species of mormyrid fish yet described.Stomatorhinus ivindoensis n. sp. est décrite de la rivière Ivindo, un affluent du fleuve Ogooué, au Gabon, Afrique Centrale. Cette espèce est caractérisée par sa très petite taille, qui ne dépasse pas 56 mm en longueur standard. Elle se distingue de S. fuliginosus du bassin du Congo, la seule espèce de Stomatorhinus décrite dont l’intervalle de taille des spécimens types est compris dans celui de S. ivindoensis, par un rapport largeur sur longueur du pédoncule caudal plus petit, une tête plus étroite, un nombre d’écailles percées le long de la ligne latérale plus grand et une nageoire caudale aux lobes arrondies. Elle se distingue de S. polli, une autre espèce similaire du bassin du Congo, par un museau plus long, un oeil plus petit, et une distance interorbitale plus grande par rapport à la longueur de la tête. Elle se distingue de S. walkeri, la seule autre espèce de Stomatorhinus décrite du